Treatment of systemic sclerosis: potential role for stem cell transplantation - Wen Xiong (Dove Medical Press, 2009)
Wen Xiong, Chris T DerkDivision of Rheumatology, Thomas Jefferson University, Philadelphia, PA, 19107, USAAbstract: Hematopoietic stem cell transplantation may “reset” the immune reconstitution and induce self tolerance of autoreactive lymphocytes, and has been explored in the treatments for systemic sclerosis. Phase I/II trials have shown a satisfactory risk benefit ratio. The true benefit will be identified by two ongoing prospective, randomized phase III trials. Multipotent mesenchymal stromal cells (MSCs) possess antiproliferative, anti-inflammatory, and immunosuppressive properties. The use of MSCs has showed successful responses in patients with severe steroid-resistant acute graft versus host disease in phase II trials, and may be a potentially promising option for patients with systemic sclerosis.Keywords: scleroderma, systemic sclerosis, treatment, stem cells, transplant